AIDS, qual o seu significado nos livros didáticos? - Frasson, Priscila Caroza (2006)
Didatic books were established in schools with the aim of improving educational work. However, in order to convert science teaching in a pedagogical task, these books standardize scientific knowledge, ignoring the richness of details and arguments of Science. Considering that, this research was based in the rhetoric and in the argumentative context of lessons on Aids and HIV of 10 didactic text books frequently utilized in high school teaching. The theme "Aids, what is its meaning in didactic text books" was elaborated in order to analyze the language of these 10 high school text books, focusing on theory of argumentation and the resources for argumentation, such as figures of style, sense, words, and thought. This project raises the questions: how does the transposition of scientific arguments about Aids and HIV to didactic books occur? What is the correlation between scientific and didactic arguments? What are the problems found in this transposition from concepts of Aids and HIV to didactic concepts? Regarding methodological procedures, it was analyzed figures of style, sense, words, and thought and their arguments about Aids and HIV. Additionally, illustrations about this theme were analyzed. In all the didactic text books analyzed, the theme was written using arguments of omnipotence, example, cause, and reciprocity. The mostly utilized arguments, the omnipotence ones, are presented to the reader (auditorium) as follows: a "fatal disease", a "lethal disease", an "illness inserted in the organisms by viruses", generating "an internal battle in the body" which is "always won by the viruses". These results indicate that, generally, the didactic text books do not present scientific arguments to the students. They define Aids as a disease and not as a syndrome, do not explain the actuation of the immunological system, do not discuss the hole of T4 cells, do not present actual images ofthe HIV structure, and do not present the real scientific models about Aids/HIV. The transposition from the scientific knowledge about Aids/HIV to the pedagogical practice keeps the didactic language of the analyzed texts to some extent with no scientific arguments. The language of these texts stays between the common sense and scientific sense; however, the common sense is more convincing than the scientific data and models.